Local Governance and Inter-municipal Cooperation - Teles, Filipe; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2016)
Territory and scale have been some of the most relevant topics in recent political science, but do we know enough about cooperation between local governments? How we think about local government has changed significantly and requires us to be equipped with new epistemological gear, considering more variables and social functions of local government than before. For instance, is inter-municipal cooperation a special arrangement? The answer is certainly positive, not as a consequence of its nature when compared to other alternatives of policy coordination and service delivery, but because it captures almost every facet of the complexity of contemporary territorial governance. Bringing relevant case-studies, previous research, and available literature together, this book will help researchers, students and practitioners with these ideas. The author provides comprehensive information about inter-municipal cooperation and identifies the main gaps in contemporary research.
Keywords: Political science; Public policy; Regional planning; Urban planning; Public administration; Political Science and International Relations; Public Policy; Political Science; Landscape/Regional and Urban Planning; Public Administration; Electronic books